Sequencing and Characterisation of Complete Mitochondrial DNA Genome for Trigonopoma pauciperforatum (Cypriniformes: Cyprinidae: Danioninae) with Phylogenetic Consideration - Hung Hui Chung,; Leonard Whye Kit Lim,; Yunshi Liao,; Tommy Tsan-Yuk Lam,; Yee Ling Chong, (Tropical Life Sciences Research, 2020)
The Trigonopoma pauciperforatum or the redstripe rasbora is a cyprinid commonly found in marshes and swampy areas with slight acidic tannin-stained water in the tropics. In this study, the complete mitogenome sequence of T. pauciperforatum was first amplified in two parts using two pairs of overlapping primers and then sequenced. The size of the mitogenome is 16,707 bp, encompassing 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes and a putative control region. Identical gene organisation was detected between this species and other family members. The heavy strand accommodates 28 genes while the light strand houses the remaining nine genes. Most protein-coding genes utilise ATG as start codon except for COI gene which uses GTG instead. The terminal associated sequence (TAS), central conserved sequence block (CSB-F, CSB-D and CSB-E) as well as variable sequence block (CSB-1, CSB-2 and CSB-3) are conserved in the control region. The maximum likelihood phylogenetic tree revealed the divergence of T. pauciperforatum from the basal region of the major clade, where its evolutionary relationships with Boraras maculatus, Rasbora cephalotaenia and R. daniconius are poorly resolved as suggested by the low bootstrap values. This work contributes towards the genetic resource enrichment for peat swamp conservation and comprehensive in-depth comparisons across other phylogenetic researches done on the Rasbora-related genus.